Laser Assisted Modified Widman Flap Surgery for the Management of Moderate to Severe Chronic Periodontitis: Diode laser modified widman flap in chronic periodontitis - Nguyen, Hong Loi; Nguyen, Viet Cuu (Journal of Lasers in Medical Sciences, 2025)
Introduction: Chronic periodontitis remains highly prevalent and often requires surgical therapy when nonsurgical approaches are insufficient. Evidence on adjunctive diode-laser use during modified Widman flap (MWF) surgery in Vietnamese patients is limited. The present study aimed to describe the clinical characteristics of Vietnamese patients with chronic periodontitis and to evaluate the 6-month outcomes of diode-laser-assisted MWF surgery. Methods: In this prospective single-arm clinical study, 41 patients (26–68 years; mean 42.0±9.8) presenting with moderate-to-severe chronic periodontitis were consecutively treated at Hue Central Hospital. After initial therapy, an MWF was performed. The wound bed and pocket walls were irradiated with an 810 nm diode laser (0.7–0.8 W, continuous mode, 30–40 s per site). Clinical variables—Plaque index (PlI), gingival index (GI), bleeding on probing (BOP %), probing depth (PD) and clinical attachment level (CAL)—were recorded at baseline, 1 week, 3 months and 6 months. Changes were analysed with paired t-test (SPSS 16.0; α=0.05). Results: Baseline mean PD and CAL were 5.99±0.53 mm and 5.19±1.06 mm, respectively. Significant improvements (P<0.01) were observed at all follow-ups. At 6 months, PD decreased by 3.07±1.63 mm and CAL gained 2.16±0.94 mm. GI dropped from 2.42±0.53 to 0.51±0.74, PlI from 2.35±0.72 to 0.56±0.90, and BOP from 77.68±17.51 % to 33.92±19.75 %. Overall, 78 % of cases achieved a “good” therapeutic response, with no serious adverse events. Conclusion: The diode-laser-assisted MWF produced substantial and sustained reductions in inflammation, plaque accumulation, pocket depth and attachment loss in Vietnamese patients with moderate-to-severe chronic periodontitis. The technique appears to be an effective surgical adjunct and warrants controlled comparative trials.